Effect of inguinal hernia on the thickness and blood flow of spermatic cord in boys. Issue 2 (3rd June 2019) - Huang, Shoujiang; Li, Canping; Yang, Xiuzhen; Liang, Jianfeng; Wang, Dongpi
Abstract : Objective: To evaluate the effect of inguinal hernia (IH) on the spermatic cord using spermatic cord ultrasonography (SCU). Methods: From January 2016 to January 2017, boys with IH who received SCU at the start of open herniorrhaphy (OH) were enrolled in this study. The age and weight at SCU, width of the spermatic cord (SC-W), peak systolic velocity (PSV) in the spermatic artery (SA-PSV) and velocity in the pampiniform plexus (PP-V), and the interval between the initial and the second OH in boys with metachronous inguinal hernia (MIH) were recorded, and the relationship among them was studied. Boys with unilateral IH comprised the IH group, and boys with MIH comprised the MIH group. Boys with polydactylism served as the control. One-way analysis of variance tested the differences among groups. Spearman's r tested the relationship between SC-W in the MIH group and the interval. Results: A total of 80 boys were enrolled in this study (IH group 29, MIH group 26, and control group 25). SA-PSV and PP-V in the hernia side were faster and slower than the control, respectively. There was no significant difference in PP-V and SA-PSV of the treated side in the MIH group and in the control group. After herniorrhaphy, SC-W was tapered down to normal size. SC-W, SA-PSV, and PP-V in the treated side were all highly correlated to the interval in a curvilinear manner. Conclusion: PSV was positively correlated with SC-W in boys with IH, and PP-V was negatively correlated; herniorrhaphy could reverse the impairment.